Recent advances and future prospects in choroideremia - Zinkernagel, Martin S (Clin Ophthalmol, 2015)
Choroideremia is a complex and rare disease that is frequently misdiagnosed due to its similar appearance to classic retinitis pigmentosa. Recent advances in genetic testing have identified specific genetic mutations in many retinal dystrophies, and the identification of the mutation of the CHM gene on the X chromosome 25 years ago has paved the way for gene replacement therapy with the first human trials now underway. This article reviews the epidemiological and pathological features of choroideremia and new prospects in imaging to monitor disease progression, as well as potential treatment approaches for choroideremia.